Kiai Leadership Strategy in Building Organizational Commitment in Pesantren - Yadi Fajri; Munirul Abidin; Achmad Khudori Soleh (Ta'dib, 2023)
This research aims to analyze the strategy of kiai in building organizational commitment in Pesantren Al Islam Kemuja Bangka and Pesantren Daarul Abror Kace Bangka. These strategic steps included how kiai laid the foundation of its organization, established closeness with subordinates, built togetherness, and appreciated subordinates' performance. This research used a qualitative approach with a case study type. To obtain research data, researchers used in-depth interviews, observation and documentation methods. Data analysis began with data condensation, presentation and ended with drawing conclusions or verification. The results of this study showed that kiais' strategies n building organizational commitment in two pesantren were different and closely related to their leadership type. In detail, the Pesantren Al Islam Bangka was led by a spiritual kiai, so that in building the commitment of the caregiver organization began with orienting the mission of the pesantren to da'wah, approaching subordinates through inspiring examples, building togetherness through close and warm communication, and appreciating subordinates with an emotionally and spiritually supportive attitude. While at Pesantren Daarul Abror Bangka, it was led by visionary kiai who build the commitment of caregiver organizations by formulating the mission of the pesantren according to the wishes of subordinates, establishing relationships by creating commensurate organizational value, building togetherness through solid teamwork, and appreciating subordinates with full delegation of authority.